DIGITAL INNOVATION IN PUBLIC SERVICE DELIVERY: AN IMPLEMENTATION STUDY OF SMART CITY INITIATIVES IN BANDUNG CITY, INDONESIA - Sofyan, Aldriantara (VISIONER : Jurnal Pemerintahan Daerah di Indonesia, 2024)
Digital innovation has become a fundamental driver in transforming public service delivery, particularly in urban governance frameworks. This study explores the implementation of smart city initiatives in Bandung City, Indonesia, through a comprehensive literature review approach. Drawing from peer-reviewed journals, policy documents, and empirical studies published in the last decade, the paper critically examines how digital technologies enhance efficiency, transparency, and citizen engagement in public services. The research adopts a thematic analysis to identify key trends, challenges, and outcomes related to smart governance and e-service platforms. Findings indicate that while Bandung has made significant strides in adopting digital solutions, persistent issues such as limited interoperability, digital divide, and regulatory gaps hinder full implementation. Moreover, the success of smart city programs appears to be closely linked to institutional readiness and cross-sector collaboration. The study highlights best practices and comparative insights from other urban centers that have advanced similar initiatives. It also underscores the importance of adaptive governance models in navigating technological disruptions. Ultimately, this review contributes to the growing discourse on digital public administration by offering evidence-based recommendations for sustainable smart city development in the Indonesian context.